Development of Sharia and Legal Studies in Australia - Ann Black (Jurnal Hukum Islam, 2022)
The study of Islamic law in Australian law schools shows positive developments. From 1997 when the first course on Islamic law was taught in at Charles Darwin University in the Northern Territory, there are now up to ten Universities that provide courses in Islamic law. This is due to several reasons, namely: 1) global and national events that require new perspectives in university culture, especially law schools; 2) law schools have the responsibility to break ties and create culturally literate citizens to maintain a harmonious multicultural society; 3) economic, political, security, tourism, education and other interests with Muslim Southeast Asian countries including Indonesia; 4) the study of Islamic Law is very important for the legal profession, especially for lawyers who will practice in areas with a significant Muslim population, or the field of international trade involving Muslim countries and; 5) Disputes involving family relations, social security rights, discrimination and immigration issues also require references to Islamic law. Harmonization of Sharia and Legal Studies in learning at the law faculty is provided by, among others: 1) the study of Islamic law becomes a component in a general comparative law course where certain features of Islamic law are highlighted for comparison with other legal models; 2) a course that combines the thematics of Islamic law with other topics, such as Law and Religion courses, or courses that focus on Islamic countries or regions, such as Law and Society in Southeast Asia, Middle East Legal Institutions, and Commercial Law. from Asia; 3) components of Islamic law are integrated into some, or all, of the legal courses taught so that the Islamic perspective becomes an inclusive part of legal education within the institution and; 4) Islamic law courses stand alone as elective courses at the Faculty of Law.